(untitled) (Journal of the College of Basic Education, 2025)
This study aims to identify the effect of the Story Face strategy on reading comprehension among fifth grade elementary students. The null hypothesis was set, stating no statistically significant difference between the experimental and control groups. The researcher employed a two-group experimental design with an end-of-test to measure reading comprehension. The experimental group studied using the Story Face strategy, while the control group studied via the traditional method. The sample consisted of 70 students equally divided, with equivalence ensured across variables such as age, intelligence, and previous grades. The researcher formulated 95 behavioral objectives according to Bloom’s taxonomy and prepared 24 daily lesson plans for each group. A test instrument comprising 24 multiple-choice items was developed, validated for face and content validity, and analyzed for difficulty, discrimination, and effectiveness of distractors. The test reliability was calculated using the Kuder-Richardson 20 formula, yielding 0.86. The study’s findings are presented in Chapter Four.